Analysis of Ground water Quality of Dahanu by Water Quality Index and Regression Analysis - Pankaj, Gogari (International Journal of Advanced Science and Technology, 2020)
Present work indicates ground water quality by quality index by Weighted Arithmetic Index Method. Total 18 groundwater samples form Dahanu and 10 water quality parameters of each sample are considered in this study. Water quality was good at ten stations and very poor and unsuitable for drinking at eight stations. High water quality index is due to high turbidity, Ca, Cl, high concentration of Fluoride. Correlation of selected parameters is analyzed and found that Electrical conductivity has significant correlation with Alkalinity, nitrite, sodium, and sulphate. Regression equations relating correlated parameters were formulated. Data was compared with Indian standard and WHO standard for drinking water.